2021
DOI: 10.3390/children8080677
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Laparoscopic Approach of Orchiopexy for Palpable Cryptorchidism: A Systematic Review and Meta-Analysis

Abstract: Background: Traditional open orchiopexy is still a standard of treatment for palpable undescended testicles. Recently several authors reported successful results using a laparoscopic approach in the treatment of palpable cryptorchidism. The present systematic review and meta-analysis investigated the utility of laparoscopic orchiopexy for palpable cryptorchidism. Methods: Scientific databases (PubMed, Scopus, Web of Science, and EMBASE) were systematically searched for relevant articles using the following ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recently, a meta-analysis revealed that laparoscopic orchidopexy has a similar results as compared with conventional orchidopexy, but with the opportunity for contralateral exploration in the case of PPV. [22] In this study, the incidence of PPV in unilateral and bilateral cryptorchidism was 74.5% and 81.7%, respectively. We used a simple method of ligating the PPV using an 18-gauge intravenous indwelling needle with a suture.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, a meta-analysis revealed that laparoscopic orchidopexy has a similar results as compared with conventional orchidopexy, but with the opportunity for contralateral exploration in the case of PPV. [22] In this study, the incidence of PPV in unilateral and bilateral cryptorchidism was 74.5% and 81.7%, respectively. We used a simple method of ligating the PPV using an 18-gauge intravenous indwelling needle with a suture.…”
Section: Discussionmentioning
confidence: 50%
“…A minimally invasive laparoscopic approach has been well described as safe and effective method in many different conditions in children [28][29][30][31][32]. Several studies showed that percutaneous gastrostomy placement has more common major complications than the laparoscopic method [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopy was more effective because two repeat orchiopexies were required in the open surgery group. Anand et al ( 66 ) conducted a systematic review and meta-analysis on the efficacy of laparoscopic testicular fixation in the treatment of palpable testis in 2021. The final meta-analysis included five studies involving 705 children, with 369 in the laparoscopic group and 336 in the open group.…”
Section: Treatment Of Cryptorchidismmentioning
confidence: 99%